2011
DOI: 10.1080/17461391.2010.551417
|View full text |Cite
|
Sign up to set email alerts
|

Maximal lactate steady‐state and anaerobic thresholds from different methods in cyclists

Abstract: The lactate anaerobic threshold (AT) determined during an incremental test has been used generally to estimate the maximal lactate steady-state intensity (MLSS int ) in several sports. Furthermore, this index could be useful to predict the time-trial cycling performance and also to prescribe training intensity to enhance aerobic capacity. The aim of this study was to compare three different AT estimations with actual MLSS int in trained cyclists. Fourteen trained cyclists participated in this study. They had p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…L -1 was the only LT derived from GXT 3 included in our analysis (bias = -6 ± 35 W). This is consistent with the results of one previous study (bias = 0.5 ± 24 W), which also recruited trained male cyclists and had a similar GXT protocol design [ 56 ]. Consistent with our findings, this study also reported that an OBLA of 3.5 mmol .…”
Section: Discussionsupporting
confidence: 92%
“…L -1 was the only LT derived from GXT 3 included in our analysis (bias = -6 ± 35 W). This is consistent with the results of one previous study (bias = 0.5 ± 24 W), which also recruited trained male cyclists and had a similar GXT protocol design [ 56 ]. Consistent with our findings, this study also reported that an OBLA of 3.5 mmol .…”
Section: Discussionsupporting
confidence: 92%
“…3 are narrower or similar to those of other studies predicting MLSS from a 1 600 m time trial (− 0.8 to 0.7 km • h − 1 or ± 6.0 % of the mean) [29], lactate minimum test (− 0.9 to 0.7 km • h − 1 or ± 6.6 % of the mean) [21,32], power output at a fixed blood lactate concentration ( ± 10.3 % of the mean) [15], power output from the minimum equivalent of the blood lactate-power relationship plus 1.5 mmol • L − 1 ( ± 9.5 % of the mean) [15], velocity associated with a respiratory exchange ratio equal to 1.00 (− 1.2 to 1.6 km • h − 1 or ± 9.0 % of the mean) [24] or ventilatory threshold (2.5 to − 1.3 km • h − 1 or ± 12.0 % of the mean) [24], in cyclists MLSS V mean (km . [15], runners [21,24] and physically active men [31,32]. This evidence adds support to the finding that MAV, together with V 80 %HRmax , provide a likely better estimation of the MLSS intensity than other lactate or ventilatory-related thresholds.…”
supporting
confidence: 86%
“…This SEE is very similar to the one previously found in soccer players (0.43 km • h − 1 , 3.5 % of the mean MLSS V ) [27] and compares favorably with other studies predicting MLSS V from the velocity corresponding to a 4 mmol • L − 1 [La − ] and velocity at the maximal constant HR maintainable for 30 min, where SEE values of 0.67 km • h − 1 (5.5 % of the mean MLSS V ) have been reported [37]. The Bland-Altman limits of agreement ( − 1.17 to 1.17 km • h − 1 or ± 7.7 % of mean MLSS V ) of equation 4 are narrower or only slightly higher compared to those of other studies predicting MLSS from a 1600 m time trial ( − 0.8 to 0.7 km • h − 1 or ± 6.0 % of the mean) [31], lactate minimum test ( − 0.9 to 0.7 km • h − 1 or ± 6.6 % of the mean) [22,34], power output at a fixed blood lactate concentration ( ± 10.3 % of the mean) [17], power output from the minimum equivalent of the blood lactate-power relationship plus 1.5 mmol • L − 1 ( ± 9.5 % of the mean) [17], velocity associated with a respiratory exchange ratio equal to 1.00 ( − 1.2 to 1.6 km • h − 1 or ± 9.0 % of the mean) [26] or ventilatory threshold ( − 1.3 to 2.5 km • h − 1 or ± 12.0 % of the mean) [26], in cyclists [17], runners [22,26] and physically active men [33,34]. This evidence lends further support to the finding that MAV, a noninvasive, cheap and objective variable, may provide a similar or better estimation of the MLSS intensity than other more sophisticated, expensive and time consuming lactate or ventilatoryrelated thresholds.…”
mentioning
confidence: 57%